Structure–function relationship in COPD revisited: an in vivo microscopy view. Issue 8 (29th January 2014) - Cosío, Borja G; Shafiek, Hanaa; Fiorentino, Federico; Gómez, Cristina; López, Meritxell; Rios, Angel; Kersul, Ana; Togores, Bernardo; Palmer, Joan; Sauleda, Jaume; Agustí, Alvar
Abstract : Background: Fibred confocal fluorescence microscopy (FCFM) is a novel technology that allows the in vivo assessment and quantification during bronchoscopy of the bronchial wall elastic fibre pattern, alveolar and vessel diameters and thickness of the elastic fibre in the alveolar wall. Aims: To relate these structural characteristics with lung function parameters in healthy subjects, smokers with normal spirometry and patients with chronic obstructive pulmonary disease (COPD). Methods: We performed FCFM in 20 never smokers, 20 smokers with normal spirometry and 23 patients with COPD who required bronchoscopy for clinical reasons. The bronchial wall elastic fibre pattern was classified as lamellar, loose and mixed pattern, and later confirmed pathologically. Airspace dimensions and extra-alveolar vessel diameters were measured. Lung function measurements and pulmonary CT scans were obtained in all participants. Results: Patients with COPD were characterised by a significantly higher prevalence of loose fibre bronchial deposition pattern and larger alveolar diameter which correlated inversely with several lung function parameters (forced expiratory volume in 1 s (FEV1 ), FEV1 /forced vital capacity ratio, maximum expiratory flow, carbon monoxide transfer factor and carbon monoxide transfer coefficient; p<0.05). Increased alveolar macrophages were demonstrated in active smokers with or without COPD. Conclusions: This is the first FCFM study to describe in vivo microscopic changes in the airways and alveoli of patients with COPD that are related to lung function impairment. These findings open the possibility of assessing the in vivo effects of therapeutic interventions for COPD in future studies.